1982
DOI: 10.1111/j.1464-410x.1982.tb13508.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Urethral Function in the Assessment of Spinal Injury Patients

Abstract: Forty-two spinal injury patients underwent single or sequential urodynamic studies to assess the value of dynamic urethral pressure using transducer tipped catheters. Three groups of patients were identified: those with poor detrusor function, those with unsustained dyssynergia and those with sustained dyssynergia. All patients demonstrated some dyssynergia. Urethral needle EMG mirrored urethral pressure changes accurately. The addition of dynamic profilometry to fluoroscopy, detrusor pressure and urethral EMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

1984
1984
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…Because there is a general agreement that electrical activ ity of the external anal sphincter is coincident with that of the external urethral sphincter in the normal subject [3], urethral pressure changes in 'static UPP' during voiding may be regarded as correlating well with electromyograp hic activity of the external urethral sphincter. And in spi nal cord injury patients, it has been reported that urethral pressure at the external sphincter zone increased coincidently with an increase of its electrical activity resulting from detrusor-sphincter dyssynergia during voiding [4][5][6]. This finding is also along the same lines as those above.…”
Section: Discussionsupporting
confidence: 79%
“…Because there is a general agreement that electrical activ ity of the external anal sphincter is coincident with that of the external urethral sphincter in the normal subject [3], urethral pressure changes in 'static UPP' during voiding may be regarded as correlating well with electromyograp hic activity of the external urethral sphincter. And in spi nal cord injury patients, it has been reported that urethral pressure at the external sphincter zone increased coincidently with an increase of its electrical activity resulting from detrusor-sphincter dyssynergia during voiding [4][5][6]. This finding is also along the same lines as those above.…”
Section: Discussionsupporting
confidence: 79%
“…La majorité des auteurs considèrent que la dyssynergie vésicosphinctérienne est pathognomonique des lésions médullaires [2][3][4][5]7,8,29]. Cependant, des dyssynergies vésico-striées sont décrites dans certaines pathologies encéphaliques : Parkinson, MSA, hémiplégie, démence, traumatisme crânien, toujours associées à une hyperactivité du détrusor [6,17,[30][31][32].…”
Section: Discussionunclassified
“…Classification de Bary [8]. Elle distingue 3 formes de dyssynergie à partir d'une évaluation urodynamique complète de 42 blessés médullaires complets et incomplets :…”
Section: Classificationsunclassified
“…Fifteen patients achieved complete voiding after placement of the first stent; 3 developed bladder Some degree of detrusor sphincter dyssynergia always accompanies suprasacral spinal injury and represents an active contraction of the outflow in association with an involuntary detrusor contraction ( Fig. 1) (Bary et a/., 1982).…”
mentioning
confidence: 99%